Deletion of the major GATA1 enhancer HS 1 does not affect eosinophil GATA1 expression and eosinophil differentiation. - Guyot, B; Valverde-Garduno, V; Porcher, C; Vyas, P (2004)
Expression of the myeloid transcription factor GATA1 is required for early stages of eosinophil differentiation. Defining mechanisms regulating eosinophil GATA1 expression will be important to understand development of this lineage. However, the cis-elements required for eosinophil GATA1 expression are not fully characterized. Previous work identified HS 1 as a major GATA1 enhancer, but its role in eosinophil GATA1 expression is unclear. Here, we show that mouse HS 1 deletion leaves eosinophil GATA1 mRNA expression and eosinophil differentiation unaffected. Chromatin isolated from eosinophils and encompassing HS 1 is weakly enriched for acetylated histones H3/H4. HS 1 deletion does not alter eosinophil GATA1 locus histone acetylation. In eosinophils, GATA1 and CCAAT/enhancer binding protein epsilon (C/EBP epsilon) do not bind HS 1 but bind selectively a cis-element in the first GATA1 intron. Thus, HS 1 is not required for eosinophil GATA1 expression. Instead, this study suggests a previously unsuspected role for the GATA1 intron element for this function.